COVID-19: Perspectives from International Studies - Morales-Camacho, María Fernanda (2022)
This thematic issue 95.2, COVID-19: Perspectives from International Studies shows the interest of our journal to offer academic spaces for understanding the dimensions and possible scope of the pandemic in the international context. Thus, the objective of gather reflections regarding political, social, and economic aspects related to this pandemic. All this is from different analytical perspectives offered by the fascinating, complex, changing, and challeging International Relations discipline within a highly connected and interdependent society.